Future thinking on power planning: A balanced model of regions, seasons and environment with a case of Taiwan. (September 2020) - Chiu, Ming-Chuan; Hsu, Hsin-Wei; Wu, Min-Ching; Lee, Meng-Ying
Highlights: A Cross-Regional and Seasonal Model is proposed considering costs and emissions. Interregional cooperation with seasonal power dispatching is the future direction. Regional factors are incorporated in possible future energy target. The coal power will be the source of flexible scheduling at peak load. Regional transmission from renewable energy has both cost and environmental benefits. Abstract: The challenges in future energy transition will be regional and seasonal nature of renewable energy and air pollution. Regional factors of air pollution involve regional equity, and only a few researches tackled long-term power planning with mitigation of air pollution. Therefore, the aim of this study is to develop a balanced long-term power planning model with compromise solutions and to decide the power generation configuration under seasonal, regional and air pollution factors in addition to cost. Based on empirical study of Taiwan, the future thinking of air pollution reduction should accept transmission from renewable energy between regions due to the cost effective and environmental benefits. The renewable energy and minor increase in non-renewable energy with better equipment will mitigate the emissions. The coal power will be the source of flexible scheduling at peak load. Interregional cooperation with seasonal power dispatching has become the future direction. A sensitivity analysis is conducted to provide suggestions when decision makers' preference change. This study can serve as a decision support system for policymakers and a platform for stakeholders to discuss future visions on power planning. Further, this model can be applied to other countries that are experiencing economic development and environmental protection dilemmas.